PERAN PONDOK PESANTREN TERHADAP FENOMENA “DISPENSASI NIKAH” (Studi Pondok Pesantren Sabilul Muttaqin Ikatrina Ponorogo) - Hana Nur Farida; Siti Nurbayani; Siti Komariyah (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This article tries to discuss the description of the roles carried out by the educational institution Sabilul Muttaqin Islamic Boarding School Ikatrina Foundation towards the rampant phenomenon of marriage dispensation in Ponorogo Regency. With descriptive qualitative methods, researchers try to explore the desired information through sources that are considered relevant to the intended study. The results of this study show that the role of the Sabilul Muttaqin Islamic Boarding School of Ikatrina Foundation is as a forum to foster religious knowledge, mental guidance and skills for children who lack attention (victims of broken homes) from their families, orphans, and children in low economic level. All of them are summarized in several activities that are carried out regularly such as the study of the Islamic books, holding reproductive health socialization, bulding education values and extracurricular activities.